1998
DOI: 10.1021/jm970730q
|View full text |Cite
|
Sign up to set email alerts
|

Potent Antagonists of Somatostatin:  Synthesis and Biology

Abstract: The search for synthetic analogues of somatostatin (SRIF) which exhibit selective affinities for the five known receptor subtypes (sst1-5) has generated a large number of potent agonist analogues. Many of these agonists display good subtype selectivities and affinities for the subtypes 2, 3, and 5, with very few selective for sst1 or sst4. Until the recent report by Bass and co-workers (Mol. Pharmacol. 1996, 50, 709-715; erratum, Mol. Pharmacol. 1997, 51, 170), no true antagonists had been discovered, let alon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 34 publications
2
54
0
Order By: Relevance
“…The data were obtained from two independent laboratories as a way to compare the biological data from different cell lines and different radioligands. The two datasets show similar results for the majority of the compounds, with some variabilities noted at hsst 3 or hsst 5 , as illustrated by the very similar values obtained in membranes of rat cortex for both sst1 and sst2 receptors (Table III), 18,19 when compared to the values obtained with recombinant human sst1 and sst2 receptors. 20,21 Typical of cyclic octapeptide analogs, the majority of our compounds showed binding to the hsst2, hsst3, and hsst5 receptors, with little or no affinity for the hsst1 or hsst4 receptors.…”
Section: Binding Affinities To the Somatostatin Receptorssupporting
confidence: 62%
See 1 more Smart Citation
“…The data were obtained from two independent laboratories as a way to compare the biological data from different cell lines and different radioligands. The two datasets show similar results for the majority of the compounds, with some variabilities noted at hsst 3 or hsst 5 , as illustrated by the very similar values obtained in membranes of rat cortex for both sst1 and sst2 receptors (Table III), 18,19 when compared to the values obtained with recombinant human sst1 and sst2 receptors. 20,21 Typical of cyclic octapeptide analogs, the majority of our compounds showed binding to the hsst2, hsst3, and hsst5 receptors, with little or no affinity for the hsst1 or hsst4 receptors.…”
Section: Binding Affinities To the Somatostatin Receptorssupporting
confidence: 62%
“…Although the potencies are still rather low, these results could represent a breakthrough in somatostatin research. [5][6][7] The synthetic somatostatin analog octreotide (Sandostatin, SMS 201-995) 8 has been studied extensively because of its therapeutic utility in the treatment of acromegaly. Octreotide provides significant therapeutic utility by producing a prolonged effect in the target organs, as a result of a much longer biological half-life.…”
Section: Introductionmentioning
confidence: 99%
“…See legend toFigure 3for other designations. * * * P , 0:001 vs UII(42,44, 46 and 47, respectively) or UII-NH 2 (43, 45 and 48, respectively) by one-way ANOVA followed by post hoc Dunnett's test, NS, not statistically significant.…”
mentioning
confidence: 94%
“…The first compound with antagonistic effects of somatostatin, c[Ahep-Phe-DTrp-Lys-Thr(Bzl)] ( Table 5, (26)) unexpectedly emerged during attempts to synthesise the Bzl-deprotected form of the pentapeptide. Initial studies showed that this peptide blocked the inhibitory effects of somatostatin on growth hormone, insulin, and glucagon release at low doses, but turned out to be an agonist at higher doses [187,188]. Some years later, Bass et al introduced disulfide-linked cyclic octapeptide antagonists which contained a DCys in position 6 and LCys in position 27 -Ac-(4-NO 2 -Phe)-c(DCys-Tyr-DTrp-Lys-Thr-Cys)-DTyr-NH 2 [189] 28 DC-38-48 Nal-c(DCys-Pal-DTrp-Lys-Val-Cys)-Nal-NH 2 [188] 29 PRL-2970 Cpa-c(DCys-Tyr-DTrp-Lys-Thr-Cys)-Nal-NH 2 [190] 30 PRL-2915 Nal-c(DCys-Pal-DTrp-Lys-Tle-Cys)-Nal-NH 2 [190] 31 AC-178,335 Ac-DHis-DPhe-DIle-DArg-DTrp-DPhe-NH 2 [191] Abbrevation: Ahp, 7-aminoheptanoyl; Nal, 3-(2-naphthyl)alanine; Cpa, 4-chlorophenylalanine; Pal, 3-pyridylalanine; Tle, tert.-leucine; 11 relative to SRIF.…”
Section: Somatostatin Antagonistsmentioning
confidence: 99%
“…Initial studies showed that this peptide blocked the inhibitory effects of somatostatin on growth hormone, insulin, and glucagon release at low doses, but turned out to be an agonist at higher doses [187,188]. Some years later, Bass et al introduced disulfide-linked cyclic octapeptide antagonists which contained a DCys in position 6 and LCys in position 27 -Ac-(4-NO 2 -Phe)-c(DCys-Tyr-DTrp-Lys-Thr-Cys)-DTyr-NH 2 [189] 28 DC-38-48 Nal-c(DCys-Pal-DTrp-Lys-Val-Cys)-Nal-NH 2 [188] 29 PRL-2970 Cpa-c(DCys-Tyr-DTrp-Lys-Thr-Cys)-Nal-NH 2 [190] 30 PRL-2915 Nal-c(DCys-Pal-DTrp-Lys-Tle-Cys)-Nal-NH 2 [190] 31 AC-178,335 Ac-DHis-DPhe-DIle-DArg-DTrp-DPhe-NH 2 [191] Abbrevation: Ahp, 7-aminoheptanoyl; Nal, 3-(2-naphthyl)alanine; Cpa, 4-chlorophenylalanine; Pal, 3-pyridylalanine; Tle, tert.-leucine; 11 relative to SRIF. One peptide (27) displayed high affinity binding to sst2 comparable to native somatostatin but reversed the somatostatin-mediated cAMP accumulation in rat somatomammotroph GH 4 C 1 cells as well as SRIFstimulated growth of sst2 expressing yeast cells.…”
Section: Somatostatin Antagonistsmentioning
confidence: 99%